Strategies for Raising Mental Health Awareness Among Students Through an Integrative Approach in School Education - Meisya Dharmawan; Juryatina; Ammar Wangyee (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: The main objective of this study is to explore strategies to increase awareness and understanding of mental health among students through an integrative approach in school education. Theoretical framework: This emphasizes the importance of mental health as a crucial component in student development, which is often overlooked in the education system. An integrative approach that combines academic, social, and emotional aspects is the foundation for creating an educational environment that supports mental well-being. Literature review: This study likely involves previous studies on the importance of mental health in education, the benefits of counselling sessions, social skills training, and community awareness activities. Methods: using a qualitative approach, with data collected through interviews, observations, and questionnaires involving students, teachers, and parents as participants. Results: The integrative approach can increase students' understanding and attention to mental health. Educational programs that include social skills training, counselling sessions, and community awareness activities have proven effective in creating an environment that supports mental well-being. Implications: The importance of integrating mental health materials into the school curriculum and the need for training for educators to create an atmosphere that cares about mental health. Novelty: lies in an integrative approach that emphasizes the integration of academic, social, and emotional aspects and multidimensional engagement, including students, teachers, and parents, in creating an educational environment that sustainably supports mental health.